Biochemical characterization and efficacy of Pleurotus, Lentinus and Ganoderma parent and hybrid mushroom strains as biofertilizers of attapulgite for wheat and tomato growth. (October 2018) - Narh Mensah, Deborah L.; Duponnois, Robin; Bourillon, Julie; Gressent, Frédéric; Prin, Yves
Abstract: Pleurotus, Lentinus and Ganoderma are mushrooms which have various properties and should be explored as bioresources for various uses such as biofertilizers for sustainable intensification of agriculture. Pleurotus, Lentinus and Ganoderma species and intra- and inter-specific/generic hybrids produced with the dual culture technique were evaluated for chitinase and esterase activities, phosphate solubilization ability, siderophore production, mycelia growth, and efficacy as biofertilizers using semi-quantitative assays. All parent and selected hybrid strains were assessed as biofertilizers in attapulgite for wheat and tomato cultivation. Correlations between biochemical characteristics, plant root and shoot biomass, and microbial loads and ergosterol content of tomato cultivation substrate post-harvest were determined. Biochemical characteristics studied were mushroom strain-specific, independent on mycelia growth rate and were altered in hybrids. Esterase production was strain-dependent and precipitates produced differed in size. This is the first report of siderophore production by P. tuber-regium, L. squarrosulus and Ganoderma sp. from Ghana as well as alteration of siderophore production by intra-species/generic and inter-generic hybrid strains. Biofertilizer efficacy of parent strains and intra- and inter-specific/generic hybrids was mushroom strain- and plant species-specific. L. squarrosulus strain SqW and P. sajor-caju strain PScW were most efficacious strains for wheat and tomato cultivation respectively. Fungal (3.65–5.40 cfu g −1 ) and bacterial (0–6.43 cfu g −1 ) colony counts after tomato cultivation varied among treatments. Ergosterol concentration in all treatments (0.07–0.96 µg g −1 ) were higher than in control treatment (0.05 µg g −1 ). Chitinase activity and siderophore production of mushroom strains positively correlated with both wheat and tomato growth. Utilization of mushrooms as biofertilizers will enhance food security. Graphical abstract: Highlights: Lentinus sp . exhibited chitinase and esterase activity and siderophore production. Enzyme activity and siderophore production were independent of mycelia growth. Intra- and inter-generic hybrids differed biochemically from parent strains. Biofertilizer potential of mushroom mycelia was strain- and plant species-specific. Chitinase and siderophore positively correlated with both wheat and tomato growth.